Construction of foundation with basement & superstructure including other civil works with finishing, internal & external plumbing & internal electrical works with other related works for 13 storied (With 3 Basements) institutional building for Brac University at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Beijing Urban Construction Group Company Ltd. for construction of foundation with Basement & superstructure including other civil works with finishing, internal & external plumbing & internal electrical works with other related works for 13 storied (With 3 Basements) institutional building for Brac University project.